Preservasi Naskah Budaya Di Museum Sonobudoyo - Hirma Susilawati (AL Maktabah, 2017)
Manuscript is one of the nation's treasures in the world, including Indonesia and is one of the cultural treasures of Indonesia. Preservation of manuscripts is needed to be carried out in various institutions or organizations that have a collection of archives or texts. The research method used by writer is descriptive method, but in data acquisition, writer do observation and direct interview to Library Museum Sonoduboyo Yogyakarta. The library of this museum has many cultural manuscripts as many as 1400an manuscripts. The preservation policy is also done in the library of this museum and the type of preservation that is done is to frezzing and converting the original manuscript to digital format for all collections. This is done for the survival of the manuscript because of the large number of visitors from students, scientists, lecturers and others using the manuscripts, access to information is open in general to all who come so that the need for preservation for manuscripts owned by the library museum Sonobudoyo.